First discovery of a Palaeoproterozoic A-type granite in southern Wuyishan terrane, Cathaysia Block: evidence from geochronology, geochemistry, and Nd–Hf–O isotopes. Issue 1 (2nd January 2017) - Chen, Zhi-Hong; Zhao, Ling; Chen, Dan-Dan; Zhao, Xi-Lin; Xing, Guang-Fu
ABSTRACT: In this study, a combined study of zircon U–Pb and Hf–O isotopes, as well as whole-rock major and trace elements and Nd isotopes has been conducted for Yangjia gneissic granite from the southern Wuyishan terrane, Southeast China, to constrain its petrogenesis and provide a new window for investigating the tectonic evolution of the Cathaysia basement. U–Pb dating for magmatic zircons yields a 207 Pb/ 206 Pb age of ca. 1.80 Ga, interpreted as the emplacement age of the Yangjia granite. The granites have relatively high K2 O, Rb, Ga, Zr, Nb, Y, and Ce contents and show low Al2 O3, CaO, and Ba concentrations. Their 10, 000*Ga/Al ratios range between 2.8 and 3.2. Zircons from the granite have ε Hf ( t ) values ranging from −13.2 to −7.2, corresponding to T Hf DM2 model ages of 2.99 Ga to 2.72 Ga. The zircon δ 18 O values range between 6.7‰ and 9.1‰ with an average of 7.7‰. In addition, the whole-rock ε Nd ( t ) values of the granites range from −6.5 to −5.4 and the T Nd DM2 model ages from 2.73 Ga to 2.82 Ga. All these geochemical and Nd–Hf–O isotopic signatures suggest an A-type affinity for the Yangjia granites, and they were likely generated by partial melting of Palaeoproterozoic parametamorphic rocks of the Wuyishan terrane in a post-collisional extensional setting. When our data is combined with existing geochronological data, it provides further evidence for the Palaeoproterozoic basement in the southern Wuyishan terrane, which records a rapid tectonic transition from post-collision to intraplate extension (1.80–1.77 Ga) related to the break-up of the supercontinent Columbia.